Pyrophosphate Scan of the Temporarily Ischemized Dog Myocardium - Duška, F.; Novák, J.; Vižďa, J.; Kubíček, J.; Kafka, P.; Veverková, O. (Nuklearmedizin - NuclearMedicine, 1981)
In 9 dogs a transient myocardial ischemia was provoked using complete occlusion of the ramus interventricularis anterior of the left coronary artery. The occlusion was removed after 5, 10 or 15 min. Four hrs after removal of the occlusion a scan of the myocardium was carried out using 99mTc-labelled pyrophosphate. In 7 out of 9 dogs under study the scan was markedly positive, in 2 dogs negative. ECG demonstrated ischemic changes practically in all dogs; the changes became normal after removal of the occlusion, namely in 5 to 35 min. The histological examination of the tissue demonstrated in all 9 dogs only a slight impairment of the myocardium.